Rare Incidental Detection Of Bombay Blood Group In A Patient Of Marfans Syndrome With Subsequent Clustering And Unusual Inheritance Pattern In Four Individuals Of Same Family In South West Region Of Punjab - Gupta, Anshul; Chhabra, Sahil; Singh, Jagsir; Dhingra, Harshi; ., Anamika; Jain, Bhaskar (Annals of Pathology and Laboratory Medicine, 2020)
The Bombay Blood Group (Oh) is characterized by absence of normal ABH antigens and presence of corresponding antibodies in serum. This blood group is suspected when a sample doesn’t show any reaction to anti-A and anti-B antibodies just like a normal O group would do but shows agglutination in reverse grouping or during antibody screening. Present case report highlights a case of 25 year old female who was incidentally detected having Bombay blood group and on further evaluation, one sibling and two first degree cousins were also detected having Bombay blood group. Such a clustering of Bombay blood group cases in a single-family is very rare and has never been reported in Punjab as per literature.